Handbook of Leisure, Physical Activity, Sports, Recreation and Quality of Life (International Handbooks of Quality-of-Life,, 2018)
This handbook provides an overview and synthesis of relevant literature related to leisure and recreation, and physical activity and its relationship to quality of life. Divided into two parts, the text presents the analysis of leisure and recreation studies and physical activities and sports, with diverse populations. The first part deals with leisure and recreation in relation to quality of life, with different perspectives on different age groups, ethnic groups, the approach of an Integrated Model of Leisure Well-being focusing on how leisure activities contribute to leisure well-being etc. The second part deals with physical activities and sports in relation to quality of life, discussing the consideration that "exercise is good for you", associating physical exercise with other conditions of life in society, its impact on people with disabilities, etc. It is of interest to researchers and students, legislators, educators, providers of leisure services. .